The Government's Role in the Success of the Village Anti-Money Politics Program in Rembang - Murtadho Yusuf, Irfan; Abdi Muhammad, Juang; Aji Imawan, Satria (Bawaslu Provinsi Kepulauan Riau, 2024)
This research examines the Election Supervisory Agency's (Bawaslu) Anti-Money Politics Village Program to increase community participation in election monitoring and combat election corruption. Using a descriptive qualitative approach, this study focuses on Rembang Regency, an area with a high risk of election violations. The implementation of the program was conducted in stages, involving a process of socialization, stakeholder coordination, and sustainability. Despite these successes, challenges such as persistent violations and the need for more supervisory personnel remain. This study highlights the effectiveness of the program in promoting democratic integrity and provides recommendations to sustain and improve the initiative in the future.